2020
DOI: 10.13106/jafeb.2020.vol7.no9.573
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Entrepreneurial Learning towards Entrepreneurial Intention of Indonesian Women

Abstract: Entrepreneurship has been the center of a worldwide phenomenon as it has contributed a lot in the economy. The researcher is trying to acknowledge the interest of Indonesian women to build their own businesses. The aim of this research is to see how entrepreneurial learning could influence Indonesian women to grow interest in doing entrepreneurial activity, with the help of three mediations: attitude toward entrepreneurship, subjective norms, and perceived behavioral control. The research will use quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
5
0
4
Order By: Relevance
“…This means that college students may already have a relatively independent idea of their future employment choices. The research of Doanh and Bernat (2019) and Hongdiyanto et al (2020) has confirmed our findings and held that SN is not an important factor in explaining EI, further pointing out that SN affects EI through EA and ESE.…”
Section: Discussionsupporting
confidence: 85%
“…This means that college students may already have a relatively independent idea of their future employment choices. The research of Doanh and Bernat (2019) and Hongdiyanto et al (2020) has confirmed our findings and held that SN is not an important factor in explaining EI, further pointing out that SN affects EI through EA and ESE.…”
Section: Discussionsupporting
confidence: 85%
“…The impact of gender on EI has been found to be significant [27,57,58]. A study dealing with the EI of students in UAE [59] also confirmed that gender affects EI.…”
Section: Gendermentioning
confidence: 75%
“…The literature review suggests that research on EI has been receiving more attention in the recent past (Hongdiyanto, et al 2020;Vuong, et al 2020;Amanamah, et al 2018;Choukir et al, 2019;Ferri, et al 2018;Jahani, et al 2018;Miao, 2016;Nabi, et al 2017;Păunescu, et al 2018). Fewer studies were found to be based in Arab countries (Aloulou, 2016;Iqbal, et al 2012;Naushad & Malik, 2018;Almobaireek, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The constituents of human capital have been studied independently or in combination. Gender has been investigated in many studies and most of them concluded that male are more inclined toward entrepreneurship (Ferri et al, 2018;Hongdiyanto et al, 2020). Entrepreneurship education, institutional environment and curriculum have been found to be influencing EI (Lu & Wang, 2018;NGUYEN, 2020;do Paço, et al 2011;Liñán et al, 2011a;Tran, et al 2018).…”
Section: Human Capital and Demographic Variablesmentioning
confidence: 99%